Characterization of allergic inflammation in chronic uterine cervicitis. (29th November 2021) - Ma, Fei; Liu, Jun; Lv, Xiaodan; Liu, Hua-Zhen; Yang, Ping-Chang; Ning, Yan
Abstract: Female genital tract chronic inflammation is common in clinics; the pathogenesis is not fully understood yet. House dust mite (HDM) involves the pathogenesis of many chronic diseases in human. This study aims to identify HDM-specific allergic response in the cervix of patients with cervical inflammation. Patients ( n = 80) with chronic cervicitis (CC) and non-CC control (NC) subjects ( n = 80) were recruited into this study. Vaginal lavage fluids (VLF) were collected from CC patients and NC subjects. Cellular components and fluid part of VLF were separated by centrifugation, and analyzed by flow cytometry and enzyme-linked immunosorbent assay. We found that a portion (52 out of 80) of CC patients responded to HDM, manifesting positive skin prick test, and HDM-specific IgE and IgG was detected in the VLF (designated CCp patients). VLF of CCp patients showed a Th2-dominant profile. HDM-specific Th2 cells were detected in VLF in CCp patients. Exposure to HDM in the culture induced proinflammatory cytokine release from CCp VLF CD4 + T cells. Exposure to CCp VLF CD4 + T cell-conditioned medium induced de novo Th2 response. Direct exposure to HDM induced allergic response in the cervix of CCp patients. In summary, a portion of CC patients respond to HDM challenge in the cervix. Exposure to HDM induces an allergy-like response in the cervix of CCp patients. Abstract : We found that 52 out of 80 patients with chronic cervicitis showed allergic response to house dust mite. House dust mite-specific Th2 cells were detected in vagina lavage fluid. Direct exposure to house dust mite antigens induced allergic response in the cervix of patients with chronic cervicitis. Graphical Abstract: